Hubungan Parental Autonomy Support dengan Career Decision-Making Difficulties pada Fresh Graduate di Kota Padang - Putra, Aditya Andhika; Dwatra, Free Dirga (Lembaga Yasin AlSys, 2025)
This study aims to examine the relationship between parental autonomy support and career decision-making difficulties among fresh graduates in Padang City. The research is grounded in the significance of parental autonomy support in helping recent graduates navigate challenges in career decision-making. A quantitative correlational design was employed, involving 385 participants who had completed their studies within the past year, selected through purposive sampling. Data were collected using two instruments: the Career Decision Difficulties Questionnaire (CDDQ) and the Parental Autonomy Support Scale (PASS), and analyzed using the Spearman-rank correlation test. The findings reveal correlations between dimensions of both variables. The autonomy support dimension is negatively correlated with lack of readiness, lack of information, and inconsistent information, indicating that higher parental autonomy support is associated with lower levels of career decision-making difficulties. Conversely, the controlling parenting dimension is positively correlated with all three difficulty dimensions, suggesting that controlling parenting styles may exacerbate barriers in the career decision-making process. These findings underscore the importance of autonomy-supportive parenting in fostering career readiness among recent graduates.